Willingness to pay for tourist services in Los Mármoles National Park, México - Melo-Guerrero, Enrique; Hernández-Ortiz, Juan; Valenzuela-Núñez, Luis Manuel; Valdivia-Alcalá, Ramón; González-Juárez, Araceli; Luna-Cervantes, Juan Oswaldo (Ecosistemas y Recursos Agropecuarios, 2022)
The objective of this research was to estimate the willingness to pay for tourist services in Los Mármoles National Park in Hidalgo State data in order to improve decision-making for both, residents and managers. The contingent valuation method was used to estimate the benefits obtained of improvements in four areas of intervention. Key stakeholders were interviewed, diagnostic workshops were organized. Furthermore, 141 tourists in 2016 and 2017 were interviewed. Based on the estimated willingness to pay, it is proposed an entrance fee to the park estimated in $1.72 USD per person. This represents an annual recreational use value in the site of $ 8 665 USD. According to the binomial logit model, the variables that influence the decision of the interviewees are: entrance fee, income level, educational level and number of companions. Biodiversity protection, forest health and fire protection were identified as the most important areas.